2014
DOI: 10.4314/ahs.v13i4.11
|View full text |Cite
|
Sign up to set email alerts
|

In vivo hypoglycemic effect of methanolic fruit extract of <i>Momordica charantia L</i>

Abstract: Background: Momordica charantia L. is a medicinal plant commonly used in the management of diabetes mellitus. Objectives: We investigated the blood glucose lowering effect of the methanolic fruit extract of the Ugandan variety of M. charantia L. in alloxan-induced diabetic albino rats. Methods: 500g of M. charantia powder were macerated in methanol and the extract administered to two groups of alloxaninduced diabetic rats. The first group received 125mg/kg, the second 375mg/kg and a third group 7mg/ kg of metf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 45 publications
2
11
0
3
Order By: Relevance
“…Indian medicinal system is a source of such plant database [2] which either in the form of powder extracts, pills or liquid forms (solutions and suspensions) has been used widely in India for treatment of various diseases. The Indian medicinal plants described in Ayurveda such as bitter melon [34] , turmeric [56] , and bael [78] , have proven their importance in recent years for treatment of various diseases, including diabetes and cancer. The development of science and technology in recent time makes it possible to discover the active constituents present in these plants and establish their biological targets for evolving them as a remedy for treating diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Indian medicinal system is a source of such plant database [2] which either in the form of powder extracts, pills or liquid forms (solutions and suspensions) has been used widely in India for treatment of various diseases. The Indian medicinal plants described in Ayurveda such as bitter melon [34] , turmeric [56] , and bael [78] , have proven their importance in recent years for treatment of various diseases, including diabetes and cancer. The development of science and technology in recent time makes it possible to discover the active constituents present in these plants and establish their biological targets for evolving them as a remedy for treating diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It is grown in India, China, Eastern Africa and South America and is used in many of these countries to treat a variety of ailments. It is important to note the stage of development of the fruit and therefore the physic-chemical properties of the polysaccharide are important in the bioactive potential for example the unripe fruit of the bitter gourd is eaten as a treatment for diabetes and scientific testing has demonstrated that it does exhibit blood glucose concentration lowering properties in both human and animal models (Kumar, Vijayalakshmi and Salimath, 2006;Nkambo, Anyama and Onegi, 2013;Palamthodi and Lele, 2014). It has been shown that water extracts from bitter gourd increase the uptake of glucose and secretion of adiponectin from fat cells (Dhiman, et.…”
Section: The Potential Role Of Cucurbit Polysaccharides In Diabetes Mmentioning
confidence: 99%
“…Even with the progress in diabetes control by synthetic drugs and insulin, research involving plants and natural products for the control and treatment of the disease is still necessary, given the high cost of drugs and their side effects as well as the popular use of plants with supposedly effective antidiabetic activities [26]. In recent years, research on plants and isolated compounds has reported antidiabetic activity of plant products [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%